Penerapan Teknologi Tepat Guna Dalam Pengembangan Budidaya Tanaman Menggunakan Metode Hidroponik Di SDN Wonosalam 1 - Hallimah Rizqi Putti; Linda Tri Andini; Oktavia Nur Qhoirunnisa; Rr. Shafira Indranovianti; Dhian Satria Yudha Kartika (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Hydroponics is a method of cultivating plants that does not use soil media but emphasizes meeting the nutritional needs of plants. Hydroponic cultivation requires less water than soil cultivation. Maintenance of hydroponic cultivation is very easy and can be done at any time regardless of the season. Cultivation of plants planted namely pakcoy. One of the advantages of growing pakcoy plants hydroponically is that they are very resistant to pests and diseases, so there is no need to control pests and diseases. The development of pakcoy hydroponic cultivation is used as an appropriate technology that is applied at SDN Wonosalam 1. The hydroponic system at SDN Wonosalam 1 is implemented as an alternative to supporting cultivation for adiwiyata classes and also as an introduction to students about hydroponic cultivation. By going through several stages of implementation, such as the initial seeding stage to the final harvesting stage, the hydroponic system involving Wonosalam 1 Elementary School students can be said to be successful in harvesting. It is hoped that this activity will provide knowledge and experience to all students of SDN Wonosalam 1